(untitled) (Journal of Entrepreneurship and Business, 2024)
This research aims to explore the implication of e-commerce application among Small and Medium (SM) Malay entrepreneurs involved in the Malaysian food and beverage manufacturing industry based on three perspectives: technology, competition, and suppliers. A survey questionnaire was developed following the three variables. Furthermore, a pilot study was conducted to identify the necessary improvements to be made to the instrument. The respondents involved SM Malay entrepreneurs who are e-commerce application users, with a 68.4% response rate. The empirical data were statistically analysed via stepwise multiple regression. Resultantly, the variables of competition and supplier influenced the implication of e-commerce application among SM Malay entrepreneurs.